Pathophysiological mechanisms in antiphospholipid syndrome. (April 2011) - Harper, Brock E; Willis, Rohan; Pierangeli, Silvia S
Antiphospholipid syndrome is a systemic autoimmune disease associated with thrombosis and recurrent fetal loss in the setting of detectable antiphospholipid (aPL) antibodies. The major antigenic target has been identified as ββ2 -glycoprotein I (ββ2 GPI), which mediates binding of aPL antibodies to target cells including endothelial cells, monocytes, platelets and trophoblasts, leading to prothrombotic and proinflammatory changes that ultimately result in thrombosis and fetal loss. This article summarizes recent insights into the role of ββ2 GPI in normal hemostasis, interactions between aPL antibodies, ββ2 GPI and cell-surface molecules, molecular prothrombotic and proinflammatory changes induced by aPL antibodies and pathogenic changes leading to fetal loss in antiphospholipid syndrome. New directions in therapy using these insights are examined.